Brittle Compressive Failure of Ice: Proportional Straining vs Proportional Loading - Schulson, E. M; Iliescu, D. (Journal of Glaciology, 2006)
Proportional straining experiments have been performed on columnar-grained S2 fresh- water ice biaxially compressed across the columns at –108C at a strain rate of (4.5 ???? 1.5) ???? 10–3 s–1. The results are compared with those obtained earlier (Iliescu and Schulson, 2004) from the same kind of material deformed to terminal failure under the same conditions, but through proportional loading. The exercise shows that the biaxial strength is practically independent of the path taken, at least under low confinement where Coulombic shear faulting limits terminal failure. First-year sea ice is expected to exhibit the same behavior.